Implementation Doping Tests Persebaya vs Mitra Kukar Match: Evaluating Anti-Doping Regulations in Indonesian Football: English - Christian Felix Lumbanraja; Rafi Satrya Arvitto (Indonesian Journal of Sports Law, 2025)
Doping tests play a crucial role in ensuring fairness and integrity in football. The implementation of these tests in the Persebaya vs Mitra Kukar match raised several legal and regulatory concerns regarding compliance with national and international anti-doping frameworks. This study examines the enforcement of doping regulations in Indonesian football, particularly in relation to FIFA and WADA standards. Using a qualitative approach, this research analyzes legal inconsistencies, procedural challenges, and their impact on players, clubs, and the league. The findings highlight the need for stricter enforcement mechanisms, better coordination among stakeholders, and improved transparency in the doping control process. The study concludes with recommendations for strengthening anti-doping policies in Indonesian football to enhance integrity and prevent future controversies. The study concludes with recommendations for strengthening anti-doping policies in Indonesian football by improving regulatory frameworks, enhancing enforcement mechanisms, and increasing collaboration between national football authorities, anti-doping agencies, and international governing bodies. Additionally, it emphasizes the importance of transparency in the doping control process, regular education for athletes and officials on anti-doping regulations, and the development of stricter sanctions for violations. These measures are essential to ensuring the integrity of Indonesian football, maintaining fair competition, and preventing future controversies that could undermine public trust in the sport.